The - Nigro, Lloyd G. (Thomson/Wadsworth, 2007)
Prepare for your career in public personnel management with THE NEW PUBLIC PERSONNEL ADMINISTRATION! With coverage of public policies, law rulings, and court rulings, this text gives you a solid foundation for advanced studies in specialized areas of public personnel management. Major policy trends and debates are discussed including affirmative action, compensation and benefits, sexual harassment, workplace violence, substance and alcohol abuse, performance appraisal, and collective bargaining. Discussion questions, suggested readings, chapter appendices, informative illustrations, and examples are just a few of the tools that will help you succeed in this course